Swimming, cycling, running and cardiovascular health - Bagheri, A.; Mohebbi, H.; Azizi, M.; Saiiari, A. (Biomechanics and Medicine in Swimming XI, 2010)
A number of epidemiological studies have proved the benefits of regular physical activity for the prevention of CHD. Exercise recommendations for health can be obtained from extrapolation between different modes of exercise. Forty non-athlete male youth participated in this study for the comparative effects of swimming, cycling and running on lipid and lipoproteins serum. In this study, after aerobic training, HDL-c increased and LDL-c decreased; so TC and TG decreased. The findings suggest that moderate training performed over many weeks induces positive changes in the plasma lipid and lipoproteins concentration in youth. However, there were differences between the three groups. Swimming, running and cycling are positive for health, although this study suggested that they have different effects.